Psychosocial predictors of non-adherence to chronic medication: systematic review of longitudinal studies - Zwikker, Hanneke E (Dove Medical Press, 2014)
OBJECTIVES: Several cross-sectional studies suggest that psychosocial factors are associated with non-adherence to chronic preventive maintenance medication (CPMM); however, results from longitudinal associations have not yet been systematically summarized. Therefore, the objective of this study was to systematically synthesize evidence of longitudinal associations between psychosocial predictors and CPMM non-adherence. MATERIALS AND METHODS: PUBMED, EMBASE, CINAHL, and PsychINFO databases were searched for studies meeting our inclusion criteria. The reference lists and the ISI Web of Knowledge of the included studies were checked. Studies were included if they had an English abstract, involved adult populations using CPMM living in Western countries, and if they investigated associations between psychosocial predictors and medication non-adherence using longitudinal designs. Data were extracted according to a literature-based extraction form. Study quality was independently judged by two researchers using a framework comprising six bias domains. Studies were considered to be of high quality if ≥four domains were free of bias. Psychosocial predictors for non-adherence were categorized into five pre-defined categories: beliefs/cognitions; coping styles; social influences and social support; personality traits; and psychosocial well-being. A qualitative best evidence synthesis was performed to synthesize evidence of longitudinal associations between psychosocial predictors and CPMM non-adherence. RESULTS: Of 4,732 initially-identified studies, 30 (low-quality) studies were included in the systematic review. The qualitative best evidence synthesis demonstrated limited evidence for absence of a longitudinal association between CPMM non-adherence and the psychosocial categories. The strength of evidence for the review’s findings is limited by the low quality of included studies. CONCLUSION: The results do not provide psychosocial targets for the development of new interventions in clinical practice. This review clearly demonstrates the need for high-quality, longitudinal research to identify psychosocial predictors of medication non-adherence.